2017
DOI: 10.1111/rego.12151
|View full text |Cite
|
Sign up to set email alerts
|

Public orchestration, social networks, and transnational environmental governance: Lessons from the aviation industry

Abstract: This article contributes to current debates on the potential and limitations of transnational environmental governance, addressing in particular the issue of how private and public regulation compete and/or reinforce each other – and with what results. One of the most influential approaches to emerge in recent years has been that of “orchestration.” But while recent discussions have focused on a narrow interpretation of orchestration as intermediation, we argue that there is analytical traction in studying orc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 78 publications
1
16
0
Order By: Relevance
“…As a whole, our analysis suggests that a government mindful of the interactions produced by its CSR interventions can orchestrate its policies to maximize its influence on business actors (Abbott et al, 2015(Abbott et al, , 2017. In line with prior political studies (Henriksen & Ponte, 2018), we found that orchestration is relevant to making sense of the regulatory efforts of not only international organizations, NGOs, or "weak" governments but also "strong" governments, such as the French government, which can and do engage in orchestration work; by regulating-in partthrough a reliance on intermediary organizations (delegated rowing), or the creative capture and shaping of standards or labels (microsteering). While subjected to a path-dependency effect, this governmental orchestration work can be deployed by a cognizant government (Knudsen & Moon, 2017), which seeks to maximize the impact of its CSR interventions while keeping their costs down (that is, most of the rowing costs are covered by intermediaries).…”
Section: Governmental Csr Interventionssupporting
confidence: 66%
See 1 more Smart Citation
“…As a whole, our analysis suggests that a government mindful of the interactions produced by its CSR interventions can orchestrate its policies to maximize its influence on business actors (Abbott et al, 2015(Abbott et al, , 2017. In line with prior political studies (Henriksen & Ponte, 2018), we found that orchestration is relevant to making sense of the regulatory efforts of not only international organizations, NGOs, or "weak" governments but also "strong" governments, such as the French government, which can and do engage in orchestration work; by regulating-in partthrough a reliance on intermediary organizations (delegated rowing), or the creative capture and shaping of standards or labels (microsteering). While subjected to a path-dependency effect, this governmental orchestration work can be deployed by a cognizant government (Knudsen & Moon, 2017), which seeks to maximize the impact of its CSR interventions while keeping their costs down (that is, most of the rowing costs are covered by intermediaries).…”
Section: Governmental Csr Interventionssupporting
confidence: 66%
“…Orchestration is defined as "the mobilization of an intermediary by an orchestrator on a voluntary basis in pursuit of a joint governance goal" (Abbott et al, 2017: 722) and refers to the enrolment of several intermediaries -through soft governance means-to achieve specific political objectives. Although this notion has primarily been used to investigate how transnational governance organizations or nongovernmental organizations (NGOs) deploy their policy activities (Abbott et al, 2015(Abbott et al, , 2017, Henriksen and Ponte (2018) show its empirical relevance to investigations on how governments coordinate many forms of interventions in the aviation industry. In this article, we focus on the mechanisms underlying the orchestration of governmental CSR interventions in financial markets.…”
Section: How Do Governmental Csr Interventions Interact: Governing Thmentioning
confidence: 99%
“…through mandating principles, transparency, and codes of conduct. Facilitative orchestration relies on softer instruments, such as the provision of material and ideational support, in order to kick-start new initiatives and/or to further shape and support them (Abbott and Snidal, 2009a, Abbott et al, 2015, Lister et al, 2015, Hale and Roger, 2014, Henriksen and Ponte, 2018, Schleifer, 2013).…”
Section: A Gvc-cognizant Approach To Orchestrating Sustainabilitymentioning
confidence: 99%
“…It can combine a variety of instruments, including: (1) intermediation, when a governor uses intermediary actors to achieve governance goals (soft instruments, indirect influence); (2) regulatory hierarchy (hard instruments, direct influence) (Abbott et al, 2015); (3) collaboration (soft instrument, direct influence); and (4) delegation (hard instruments, indirect influence) (Green, 2013). Public orchestrators may thus combine straight regulation (or the threat of future/stronger regulation) with collaboration, delegation, intermediation and other hybrid mechanisms, such as placing their own representatives in key positions in intermediary organizations (Henriksen and Ponte, 2018), or harnessing civil society pressure and consumer influence, to achieve specific environmental benefits. What we lack so far in existing public orchestration approaches is an understanding of the GVC factors that shape sustainability governance and a clearer set of options on how this knowledge can be used strategically and with what limitations.…”
Section: A Gvc-cognizant Approach To Orchestrating Sustainabilitymentioning
confidence: 99%
“…In addition to threatening human lives, accidents are often associated with severe environmental and pollution consequences [ 3 ]. Therefore, the environment and safety have always been of interest to engineers in this industry [ 1 , 2 , 3 , 4 ]. Process optimization can be effective in solving these problems and their impact on public health [ 2 , 5 ].…”
Section: Introductionmentioning
confidence: 99%